Multi-parametric characterization of proton bunches above 50 MeV generated by helical coil targets - P. Martin; H. Ahmed; O. Cavanagh; S. Ferguson; J. S. Green; B. Greenwood; B. Odlozilik; M. Borghesi; S. Kar (High Power Laser Science and Engineering)
Tightly focused proton beams generated from helical coil targets have been shown to be highly collimated across small distances, and display characteristic spectral bunching. We show, for the first time, proton spectra from such targets at high resolution via a Thomson parabola spectrometer. The proton spectral peaks reach energies above 50 MeV, with cutoffs approaching 70 MeV and particle numbers greater than 10